REALITAS STRES PADA PERAWAT DI PUSKESMAS SIANTAN TENGAH, KEPULAUAN ANAMBAS - Dharma Jaya Hartono; Vip Paramarta (Journal of Innovation Research and Knowledge, 2024)
The research conducted was about the Reality of Stress in Nurses at the Siantan Tengah Community Health Center. This study aims to determine the description of nurses' work stress and determine the factors that affect nurses' work stress. This research is descriptive research with qualitative methods. In this study, the determination of research subjects used purposive sampling method. Based on the results of research conducted using interviews and documentation techniques, it is found that nurses have high work stress due to high enough workloads, where in addition to being clinicians, nurses must also fill activities outside the Community Health Center such as counseling and health promotion at Integrated Servvice Post / Posyandu (Toddlers, Adolescents, Elderly), screening of school children, socialization and mobile health centers, and also fill positions in management, and each nurse should hold 1 work program but sometimes a nurse gets several work programs so that the three subjects often experience unstable emotions when they go home to meet their families and sometimes lose focus in carrying out their work